Rapid and Specific Detection of Active SARS-CoV-2 With CRISPR/Cas12a - Liu, Xinyi; Li, Yanhua; Wang, Xin; Song, Yifan; Wu, Lina; Yu, Benyuan; Ma, Xiaodong; Ma, Peixiang; Liu, Ming; Huang, Xingxu; Wang, Xinjie (Frontiers in Microbiology, 2022)
Rapid and sensitive nucleic acid detection of SARS-CoV-2 has contributed to the clinical diagnosis and control of COVID-19. Although detection of virus genomic RNA (gRNA) has been commonly used in clinical diagnosis, SARS-CoV-2 gRNA detection could not discriminate between active infectious virus with remnant viral RNA. In contrast to genomic RNA, subgenomic RNAs (sgRNAs) are only produced when the virus is actively replicating and transcription, detection of sgRNA could be considered as an indication to evaluate infectivity. CRISPR/Cas-based nucleic acid detection methods have been considered as potential diagnostic tools due to their intrinsic sensitivity, specificity and simplicity. To specifically detect active virus replication, in this study, we developed a CRISPR-based active SARS-CoV-2 (CRISPR-actCoV) detection strategy by detecting sgRNAs of SARS-CoV-2. CRISPR-actCoV combined reverse-transcription recombinase polymerase amplification (RT-RPA) with CRISPR Cas12a-assisted fluorescence reporter system, enables detection of sgRNAs as low as 1 copy in 35 min with high specificity, the detection results can be read with naked eyes. Further, we performed CRISPR-actCoV mediated sgRNA detection in 30 SARS-CoV-2 potentially infected clinical samples, 21 samples were SARS-CoV-2 sgRNA positive. A quantitative RT-PCR assay was also performed to detect gRNA of SARS-CoV-2 in parallel, among the 30 clinical samples, 27 samples were gRNA positive. Taken together, CRISPR-actCoV provides an alternative for rapid and accurate detection of active SARS-CoV-2 and has great significance in better response of coronavirus causing epidemic disease.